Links between community ecology theory and ecological restoration are on the rise. Issue 2 (23rd August 2017) - Wainwright, Claire E.; Staples, Timothy L.; Charles, Lachlan S.; Flanagan, Thomas C.; Lai, Hao Ran; Loy, Xingwen; Reynolds, Victoria A.; Mayfield, Margaret M.
Abstract: Community ecology is frequently invoked as complementary to and useful for guiding ecological restoration. While the conceptual literature is devoted to this unification, first‐hand accounts from practitioners and ecologists suggest that integration may be weak in practice. To date, there have been no analyses of how extensively community ecology theory appears in the empirical restoration literature. We address this knowledge gap with the first quantitative assessment of the extent to which community ecology concepts appear in empirical restoration literature by analysing the use of community ecology theories, concepts and conceptually derived tools in the design and interpretation of 1, 000+ experimental ecological restoration studies over time (20 years) across all global regions. We also gauge general trends in author demographics, focal ecosystems and taxa targeted by these studies. We found that the incorporation of community ecology into restoration research has increased significantly in recent years. Community assembly and succession theories were the community ecology concepts integrated most often, while the functional traits framework and evolutionary theory have increased in usage recently. Synthesis and applications . Restoration endeavours are increasingly infused with elements of community ecology. Our results highlight the widespread application of deterministic models of community structure in restoration design and the rise of ecosystem service and function‐focused restoration. With this diagnostic summary of these applications, ecologists and restoration practitioners can move forward while directly exploring underdeveloped synergies between theory and practice. Abstract : Restoration endeavours are increasingly infused with elements of community ecology. Our results highlight the widespread application of deterministic models of community structure in restoration design and the rise of ecosystem service and function‐focused restoration. With this diagnostic summary of these applications, ecologists and restoration practitioners can move forward while directly exploring underdeveloped synergies between theory and practice.